Anisakis physeteris larvae and other helminths in coryphaena hippurus "Perico" sold in Ventanilla fisheries market, Callao, Perú - Cabrera, Rufino (2002)
The aim of this study was to determine the prevalence and mean intensity of infection by the nematode Anisakis physeteris larvae and other helminths according to size and sex. The study was performed on 57 specimens of Coryphaena hippurus selected at random in “Ventanilla” Fisheries Market, Callao, Peru in May 2002. The prevalence and the mean intensity to A. physeteris larvae were of 33,33% and 1,37; to Hysterotylacium sp., adult and larvae were 100% and 88,93%; to Tentacularia coryphaenae metacestods were 71,92% and 6,44; to Nybelinia sp., were 19,29 and 2,64; to Bathycotyle coryphaenae trematods were 28,07% and 2,25 and to Dinurus spp., were 22,81% and 3,42, respectively. The fishes between 127-130 cm of size were the most parasitized by A. physeteris larvae. This species was prevalent in the evaluated population and in spite of the low mean intensity, there is a risk to contract anisakidosis if raw or uncooked C. hippurus is eaten.